"The Touch of Civilization" : Comparing American and Russian Internal Colonization - Sabol, Steven (Book collections on Project MUSE., 2016)
"A critical, comparative examination of internal colonization exercised by the United States and Russia and experienced by two indigenous populations, the Sioux and the Kazakhs, to negate the tendency to isolate the study of American history, to overemphasize the uniqueness of the American development and to exalt national pride"--Provided by publisher.